Vascular Contributions to Migraine: Time to Revisit? - Mason, Bianca N.; Russo, Andrew F. (Frontiers in Cellular Neuroscience, 2018)
Migraine is one of the most prevalent and disabling neurovascular disorders worldwide. However, despite the increase in awareness and research, the understanding of migraine pathophysiology and treatment options remain limited. For centuries, migraine was considered to be a vascular disorder. In fact, the throbbing, pulsating quality of the headache is thought to be caused by mechanical changes in vessels. Moreover, the most successful migraine treatments act on the vasculature and induction of migraine can be accomplished with vasoactive agents. However, over the past 20 years, the emphasis has shifted to the neural imbalances associated with migraine, and vascular changes have generally been viewed as an epiphenomenon that is neither sufficient nor necessary to induce migraine. With the clinical success of peripherally-acting antibodies that target CGRP and its receptor for preventing migraine, this neurocentric view warrants a critical re-evaluation. This review will highlight the likely importance of the vasculature in migraine.